أثر نظام معلومات الموارد البشرية على ممارسات الموارد البشرية دراسة بالبنوك التجارية الليبية - عمر المختار مصباح أبوزيد; عبدالسلام العزومي عبدالسلام (Surman Journal of Science and Technology, 2025)
The purpose of this study is to find out the impact of human resources management practices on human resources information system. The researcher has used three independent variables to present human resources management practices, which are human resources planning, employment, and human resources training. The study was applied to the Republic and National Commercial Bank. The data collected through questionnaire instrument from 285 employees. The study found significant and positive relationships among the (Human Resources Planning, Employment, and Human Resources Training) variables and the Human Resources Information System. The r values for these relationships were 0.301, 0.211, and 0.208 respectively. As a final conclusion, it can point out that the achievement of the objectives proposed in this paper has allowed the researcher to empirically prove that, in the Republic and National Commercial Bank of Libya, there is a relationship between human resources practices and human resources information system.